Frações húmicas em luvissolos sob diferentes sistemas agroflorestais no município de Sobral - CE. - Morais, Gislane Mendes de (2007)
Investigations about agroforestry systems, which has been carried out in the arid region in Ceara, Brazil, comparatively to a conventional tillage system in the same area, showed an increase in the concentration of fulvic fraction (FAF) and humic acid (FAH) fractions. These results are related to the conditions in which soil was plowed similar to what is usually done in agrosilvopastoral and conventional systems, which might be attributed to a possible conversion of the humin fraction into FAF and FAH. To address to this hypothesis, a field experiment was carried out aiming to characterize the humic fractions of a Luvissol, over the following treatments: Agrosilvopastoral system (AGP), Silvopastoral system (SILV), Fallow conventional tillage (CIP), Native forest 1 (MN1) and Native forest 2 (MN2), at the depths of 0 to 6 and 6 to 12 cm of the soil. Termogravimetric, elemental, visible-ultraviolet and infrared analyses were utilized to characterize FAF and HAF in the soil samples. The results showed humic acids to be more resistant than fulvic acids. Silvopastoral system had its FAH less resistant in comparison to the others. The AGP had the FAH more humified, which may be more recalcitrant. This finding might be related, due to the AGP to overgo impact by the adopted management, what does not take place in the SILV, so that it might confirm the hypothesis that soil environment overgoing intense disturb might be under degradation.